2011
DOI: 10.1124/dmd.111.043083
|View full text |Cite
|
Sign up to set email alerts
|

Species Comparison of In Vivo P-Glycoprotein-Mediated Brain Efflux Using mdr1a-Deficient Rats and Mice

Abstract: ABSTRACT:The experiments described herein compared the extent of in vivo P-glycoprotein (P-gp)-mediated brain efflux between rats and mice for a set of known central nervous system compounds. With use of newly introduced genetically modified mdr1a-deficient rats and their gene-competent counterparts, the brain to plasma distribution was assessed and compared with the distribution pattern in mdr1a-deficient and wild-type mice. Four compounds (aripiprazole, citalopram, risperidone, and venlafaxine) were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 35 publications
4
32
0
Order By: Relevance
“…Independent studies established that SAGE Mdr1a knockout rats exhibited increased brain distribution of seven P-glycoprotein (P-gp) substrates quantitatively consistent with established murine models (Bundgaard et al, 2012), and SAGE Bcrp knockout rats showed expected increases in oral absorption and decreased biliary excretion of relevant probes (Huang et al, 2012). Proprietary Mdr1a knockout rats generated in the Wistar strain also exhibited increased oral absorption and central nervous system distribution of P-gp substrate drugs (Chu et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Independent studies established that SAGE Mdr1a knockout rats exhibited increased brain distribution of seven P-glycoprotein (P-gp) substrates quantitatively consistent with established murine models (Bundgaard et al, 2012), and SAGE Bcrp knockout rats showed expected increases in oral absorption and decreased biliary excretion of relevant probes (Huang et al, 2012). Proprietary Mdr1a knockout rats generated in the Wistar strain also exhibited increased oral absorption and central nervous system distribution of P-gp substrate drugs (Chu et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
“…Together, these data show that clearance of drugs that are not substrates of the knocked-out transporter can be 30-60% higher in SAGE knockout rats, which correlate with the 22-53% increase in liver and kidney relative weights. However, this trend of modestly decreased exposure of nonsubstrate drugs resulting from increased clearing capacity is irrelevant to the study of efflux transporter-mediated pharmacokinetics, whose goal is to identify increases in exposure (Bundgaard et al, 2012;Chu et al, 2012;Huang et al, 2012;Zamek-Gliszczynski et al, 2012a). Finally, prediction of the drug-interaction potential is based on the increase in exposure in the relevant knockout versus wild-type controls (Zamek-Gliszczynski et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zamek-Gliszczynski et al (2012) reported that the brain distribution of paclitaxel was markedly enhanced in Mdr1a knockout rats. In addition, Bundgaard et al (2012) found that the brain distribution of several central nervous system drugs and active metabolites showed the same changes in brain penetration in rats as in mice when Mdr1a knockout animals were compared with wild-type animals. Liu et al (2014) have recently used a cassette-dosing approach to study BCRP and P-gp substrates and inhibitors in Mdr1a knockout rats.…”
Section: Introductionmentioning
confidence: 93%
“…Knockout rats have advantages compared with previously established mouse knockout models (Kodaira et al, 2010;Bundgaard et al, 2012) due to the high relevance of rats for toxicological testing during preclinical drug development and their better suitability for pharmacokinetic studies using repeated blood sampling.…”
Section: Introductionmentioning
confidence: 99%